Mature seeds for in vitro sanitation of the Grapevine leafroll associated virus (GLRaV-1 and GLRaV-3) from grape (Vitis vinifera L.) - Peiró, Rosa; Gammoudi, Najet; Yuste, Alberto; Olmos, Antonio; Gisbert, Carmina (Spanish Journal of Agricultural Research, 2015)
The conservation of old grapevine varieties is important since they are adapted to specific climate conditions and may carry genes interesting to breeders. As virus infection is common in grapevine varieties, the use of virus free materials is of great importance. In this work, we used somatic embryogenesis for the sanitation of GLRaV-1 and GLRaV-3 viruses that were found after analyzing the putative presence of the five most common, economically important grape viruses by real-time multiplex RT-PCR in the old cultivar “Grumet Negre”. Unopened and opened inflorescences, fecundated ovaries, and, also, mature seeds were used as starting explants. Explants were cultured on plates with two embryogenesis induction media (Nitsch & McCown Woody plant medium) that contained the growth regulator thidiazuron and differed in their salt and vitamin compositions. One half of each kind of explant was cut prior to being cultured. After five months of culture, embryos had only developed from seeds that were cut previous to sowing. To the best of our knowledge, this is the first time that mature seeds have been used for inducing embryogenesis in grape. A total of 42% of the embryos transferred to tubes for germination regenerated into normal plantlets. The absence of both the GLRaV-1 and GLRaV-3 viruses in all regenerated plants was confirmed by real-time uniplex RT-PCR. So, this protocol can be used for sanitation and also for micropropagation.